The Urgency of Meaningful Participation in the Law Making Process from the Perspective of Democratic Countries (Comparison of Indonesia, South Africa and the United States) - Rengga Kusuma Putra; Aziz Widhi Nugroho; Geofani Milthree Saragih; Siti Fatimah; Satriya Nugraha (Faculty of Law, Universitas Pekalongan, 2025)
Meaningful participation in law formation is a crucial aspect of a democratic country. The existence of this participation not only reflects the voice of the people but also increases the legitimacy of the resulting law. A legislative process that involves the community can create rules that are more responsive and in line with community needs. In this context, this research discusses meaningful participation practices in Indonesia, South Africa, and the United States. Each country has different approaches and mechanisms for involving the public in the legislative process. The research method used is normative legal research with a statutory approach and a comparative legal approach. Through this approach, the study analyzes the laws and regulations governing public participation and identifies best practices from each country. The research results show that South Africa implements an effective public consultation system, where the public can provide direct input in the discussion of draft laws. Meanwhile, the United States has a structured participation mechanism, including public hearings and gathering input from various stakeholders, thereby creating a space for constructive dialogue between policymakers and the public. On the other hand, Indonesia still faces challenges in ensuring meaningful participation, despite efforts through public discussion mechanisms. These findings suggest the need to improve participation mechanisms in Indonesia to optimize the quality of democracy and legal legitimacy. Apart from that, support from the government and society is needed to create a stronger culture of participation, so that every individual feels they have a role in the legislative process. In this way, it is hoped that the resulting law will not be just a formality, but wil.Keywords:Meaningfull Participation; Legislation; Law Making; Democratic.